The effect of the guided imagination strategy on developing spatial and natural intelligence The second graders have an average in geography (Journal of the College of Basic Education, 2020)
The current study aims to identify the effect of the strategy of imagination guided in the development of spatial and natural intelligence for the second stage / secondary school in geography, The current study was adopted in Baghdad, the researcher selected a sample from all students from general directorate of education /Al- Rafa. The sample of the current study consists of 60 students, the sample was divided into two groups (experimental and control group). The groups are statistically equalized in a number of variables such as age, spatial and natural intelligence, The researcher used statistical tools which consisted of 40 items. To ensure the validity of this tool and to verify its characteristics, the researcher used a t-test for independent groups. The results of the current study came up that the experimental group is better in their performance than the control one. In the conclusion of this study, recommendations and suggestions for further studies have been put forward.